Molecular phylogeny of the “salty” Liolaemus species (Reptilia: Squamata): anomalus group, endemic of the Argentina Monte Desert - Morando, Mariana (2021)
In Argentina, the Monte ecoregion extends for more than 2,000 km from NW Argentina to boreal Patagonia, and includes many salt-pans and barren flatlands colonized by the monophyletic Liolaemus anomalus group that includes seven species. Some of their external morphological characteristics and behaviors are very unusual for the genus, and this has led to a complex taxonomic history. The group is very poorly known except for a recent paper with descriptions of three species and morphological-based phylogenetic hypotheses. Of the four recognized species, two are threatened and one is vulnerable, and while the conservation status of the three recently described species is unknown, they are suspected to also be under some degree of threat. We reviewed all georeferenced localities known to produce a distribution map, and sequenced two mitochondrial and four nuclear genes, for representatives of all species. We inferred a time-calibrated species tree showing that the evolutionary history of this clade occurred entirely during the Pleistocene, with most of the divergences very recent. The climatic and geomorphological changes driving this divergence started during the Great Patagonian Glaciation, initially separating the two northwestern-most distributed species (L. pipanaco + L. pseudoanomalus) from the rest. Given the very recent evolutionary history of the group and their unique and conserved morphology, incongruent topologies among datasets are expected; a detailed genome-wide dataset will be needed to fully assess and resolve their speciation history.